THE EFFECT OF THE TWO STAY TWO STRAY (TSTS) LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN GRADE IV PPK SUBJECTS AT UPTD SPF SD NEGERI 1 RIMO - Nuraya, Sopi; Safiah, Intan; Yamin, M. (Elementary Education Research, 2025)
The process of teaching and learning activities is still teacher-centered. However, in reality, students should be expected to be more active and play a bigger role in the teaching and learning process, while teachers are only facilitators for students. As a result, students' learning outcomes, especially grades in PPKn subjects, tend to be low. Students were less enthusiastic and there was no question and answer process during the discussion in participating in PPKn learning, because it was considered a boring lesson and difficult to understand... so the Two Stay Two Stray learning model was used. The formulation of the problem in this research is "Is there an influence of the Two Stay Two Stray (TSTS) learning model on student learning outcomes in grade IV civics subjects at UPTD SPF SD Negeri 1 Rimo?". This research aims to determine the effect of the Two Stay Two Stray (TSTS) learning model on student learning outcomes in class IV civics subjects at UPTD SPF SD Negeri 1 Rimo. The approach used in this research is a quantitative approach, the type of research is Quasi Experimental Design with a Nonequivalent Control Group Design. Sampling used a total sampling technique with class IVA as the experimental class and IVB as the control class, with each class consisting of 30 students. This research instrument is a multiple choice test with 20 questions. The data collection technique uses tests in the form of pretest and posttest, data analysis techniques use SPSS 26 and hypothesis testing uses the independent sample t-test. The results of the independent t-test obtained a significance value (2-tailed) of 0.001 0.05. So the decision making criteria are Ha accepted and Ho rejected. So, it can be concluded that there is an influence of the two stay two stray (TSTS) learning model on learning outcomes in class IV civics subjects at UPTD SPF SD Negeri 1 Rimo.